2005
DOI: 10.1176/appi.psy.46.6.549
|View full text |Cite
|
Sign up to set email alerts
|

Nonpsychiatric Medical Treatment of Body Dysmorphic Disorder

Abstract: Many individuals with body dysmorphic disorder seek nonpsychiatric medical and surgical treatment to improve perceived defects in their physical appearance. However, the types of treatments sought and received, as well as the treatment outcome, have received little investigation. This study describes the frequency, types, and outcomes of treatments sought and received by 200 individuals with body dysmorphic disorder. Treatment was sought by 71.0% and received by 64.0%. Dermatological treatment was most frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
150
0
33

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(189 citation statements)
references
References 17 publications
6
150
0
33
Order By: Relevance
“…Претставува често пореметување и опфаќа 1.7 -2.4% од светската популација. Во однос на половата зафатеност, кај разгледувани студии се движи од 1:1 до 3:2 и тоа жени во однос на мажи [1]. Меѓутоа најдено е во големи епидемиолошки студии дека БДД има повеќе сличности во однос на различности кога се работи за полова разлика, така да како заклучок може да се каже дека мажите и жените се скоро подеднакво зафатени со ова заболување.…”
Section: воведunclassified
“…Претставува често пореметување и опфаќа 1.7 -2.4% од светската популација. Во однос на половата зафатеност, кај разгледувани студии се движи од 1:1 до 3:2 и тоа жени во однос на мажи [1]. Меѓутоа најдено е во големи епидемиолошки студии дека БДД има повеќе сличности во однос на различности кога се работи за полова разлика, така да како заклучок може да се каже дека мажите и жените се скоро подеднакво зафатени со ова заболување.…”
Section: воведunclassified
“…For patients with BDD these treatments typically fail to alleviate distress (Crerand, et al, 2005;Phillips, Grant, Siniscalchi, & Albertini, 2001). Investigators have found that 48% to 76% of patients with BDD sought cosmetic surgery, dermatological treatment, or dental procedures (Crerand, et al, 2005;Phillips, et al, 2001; and 26% received multiple procedures .…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 99%
“…27 Em média, pessoas com o TDC relatam preocupações com cinco a sete partes do corpo durante o curso do transtorno. 28 Os pacientes relatam incapacidade para interromper os pensamentos sobre sua percepção do defeito, sendo difícil controlar tal obsessão, que pode tornar-se mais intensa em situações nas quais o indiví-duo sente-se pressionado pela expectativa de ser observado, como em situações sociais. 29 Tentando reduzir o estresse causado pelas suas crenças, os pacientes utilizam estratégias que geralmente tem pouco ou nenhum sucesso.…”
Section: Clínica Do Transtorno Dismórfico Corporalunclassified
“…48 Não existem estudos de pacientes, nas populações que procuram tratamento cosmético com profissionais paramédicos, mas alguns sugerem que pacientes com o TDC, com frequência, buscam esses profissionais. 28,49 O estudo de Kittler et al 50 apontou que pacientes obesos também podem apresentar o TDC e, com o desenvolvimento da cirurgia bariátrica, nos últimos anos, tem havido grande procura por tratamentos cosméticos para melhorar as consequências da redução drástica de peso. No entanto, pouco se sabe sobre os aspectos psicológicos desses pacientes.…”
Section: Transtorno Dismórfico Corporal Em Outras Populações Médicasunclassified